Wind characteristics and flutter performance of a long-span suspension bridge located in a deep-cutting gorge. (15th April 2021) - Hu, Peng; Han, Yan; Cai, C.S.; Cheng, Wei
Highlights: The inhomogeneous wind fields at the bridge site were measured in detail by wind tunnel tests. The wind coherence along the bridge girder was determined in three situations. The inhomogeneous wind attack angles decrease the critical flutter velocity of the bridge. Abstract: The wind characteristics as well as the flutter performance of a long-span suspension bridge located in a deep-cutting gorge terrain were investigated in the present study. To address the spatially variable or inhomogeneous wind fields (InWF) at the bridge site, a large terrain model surrounding the bridge site was installed in a large-scale wind tunnel. The mean wind speed, turbulence intensity, wind attack angle, wind power spectral density (PSD) and wind coherence all varying along the bridge girder were measured and analyzed in detail. Also, the stationarity and the cumulative distribution functions of the turbulent flow along the bridge girder were evaluated. Then, the flutter performance under four different InWF cases were comprehensively investigated. The results show that the turbulence components u as well as w along the bridge girder can be considered as stationary Gaussian stochastic processes. The wind PSDs significantly vary along the bridge girder, and the traditional wind PSDs obtained from the relatively flat terrains are not accurately applicable here. A two-parameter root coherence function model was developed to address the complex wind coherence over the deep-cutting gorge, and the wind coherence along the bridge girder was determined in three situations. When the wind fields along the bridge girder are assumed as homogeneous, the critical flutter velocity is overestimated by 10.1%. When inhomogeneous wind attack angles are considered, the contribution of the first symmetrical torsional mode to the critical flutter state become larger.